Talk vs. actions : using a Q-sort to study an evolutionary view of same sex friendships. - Hendricks, David C. (My University, 2008)
This study sought to find out whether there are differences between male and female same-sex friendships based on evolutionary theory. The researcher took a self-referent measure known as the Q-Sort. The Q-Sort was administered in a more "user-friendly" computer program instead of the traditional method. Significant differences were found between of female analogs being descriptive for female participants. However, there was no significant differences in analog preference for male participants' same-sex friendships. Female participants tended to have same-sex friends that had "feminine" traits, whereas male same-sex friends did not prefer masculine or feminine traits in friends. This means that female same-sex friendships tend to fit the evolutionary theory predictions whereas; males prefer same-sex friendships that have a mix of sex based characteristics.
Keywords: Female friendship; Male friendship; Male college students; Women college students; Q technique; Sex differences (Psychology)